Tunnelling Into a Sustainable Future – Methods and Technologies : Proceedings of the ITA-AITES World Tunnel Congress 2025 (WTC 2025), 9-15 May 2025, Stockholm, Sweden - Fredrik Johansson; Anders Ansell; Daniel Johansson; Johan Funehag; Jenny Norrman (CRC Press, 2025)
Tunnelling into a Sustainable Future – Methods and Technologies contains the contributions presented at the ITA-AITES World Tunnel Congress 2025 (Stockholm, Sweden, 9-15 May 2025). The contributions cover a wide range of topics in the fields of tunnelling and underground engineering, including:1. Innovating tunneling2. Safety Underground3. Use of underground space4. Investigations and ground characterisation5. Planning and design of underground space6. Conventional tunnelling7. Mechanised tunnelling8. Complex geometries including shafts and ramps9. Grouting and groundwater control10. Instrumentation and monitoring11. Operation, inspection and maintenance12. Contractual aspects, financing and risk management13. Impact from climate changeTunnelling into a Sustainable Future – Methods and Technologies will serve as a valuable reference to all concerned with tunnelling and underground engineering, including students, researchers and engineers.